2022
DOI: 10.3390/nu14040758
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Analysis of the Nutritional and Health Status among Children and Adolescents in Eastern China

Abstract: We aimed to identify multiple nutritional health problems and the relevant factors among children and adolescents aged 7–17 years. This study was part of the China Nutrition and Health Surveillance of Children and Lactating Mothers in 2016–2017, conducted in Jiangsu Province in eastern China. After sampling, 3025 school-age children and adolescents were enrolled into this study. Demographic information collections and anthropometric measurements were conducted by trained local Center for Disease Control and Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Anemia prevalence in 0–18-year-old children from China in national [ 30 , 31 , 47 ] and subnational studies (mostly covering the western region) ranged from 2.7 to 86%, and ID prevalence ranged from 7.3% to 62% [ 50 , 52 , 55 , 56 , 57 , 60 , 61 , 64 , 65 , 67 , 68 , 75 , 87 , 95 , 97 , 102 , 103 , 105 ]. The prevalence of anemia in children decreased with age ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Anemia prevalence in 0–18-year-old children from China in national [ 30 , 31 , 47 ] and subnational studies (mostly covering the western region) ranged from 2.7 to 86%, and ID prevalence ranged from 7.3% to 62% [ 50 , 52 , 55 , 56 , 57 , 60 , 61 , 64 , 65 , 67 , 68 , 75 , 87 , 95 , 97 , 102 , 103 , 105 ]. The prevalence of anemia in children decreased with age ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of zinc deficiency in children (6–11 years) from CHNS 2011-12 was reported at 10% [ 35 ]. A recent study by Tian et al, 2020, reported zinc deficiency in children (7–17 years) at 4.8% in Jiangsu province, eastern China [ 95 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among those, the classifications of residence, age group, and Engel’s coefficient were consistent with our previous study [ 21 ]. Physical activity was grouped as low level (0–3 days/week), high level (≥4 days/week), and none [ 36 ]. Both the passive smoking and alcohol drinking status were divided into 2 groups (yes and no).…”
Section: Methodsmentioning
confidence: 99%